Accurate approximate solution of partial differential equations at off-mesh points. - Enright, W. H. (ACM transactions on mathematical software.)
Numerical methods for partial differential equations often determine approximations that are more accurate at the set of discrete meshpoints than they are at the ?off-mesh? points in the domain of interest. These methods are generally most effective if they are allowed to adjust the location of the mesh points to match the local behavior of the solution. Different methods will typically generate their respective approximations on incompatible, unstructured meshes, and it can be difficult to evaluate the quality of a particular solution, or to visualize important properties of a solution. In this paper we will introduce a generic approach which can be used to generate approximate solution values at arbitrary points in the domain of interest for any method that determines approximations to the solution and low-order derivatives at meshpoints. This approach is based on associating a set of ?collocation? points with each mesh element and requiring that the local approximation interpolate the meshpoint data and almost satisfy the partial differential equation at the collocation points. The accuracy associated with this interpolation/collocation approach is consistent with the ?meshpoint accuracy? of the underlying method. The approach that we develop applies to a large class of methods and problems. It uses local information only and is therefore particularly suitable for implementation in a parallel or network computing environment. Numerical examples are given for some second-order problems in two and three dimensions.